Pepsin extraction from bovine stomach using aqueous two-phase systems: Molecular mechanism and influence of homogenate mass and phase volume ratio - Imelio, Natalia (2008)
Pepsin partitioning, a gastric acid protease, in aqueous two-phase systems of polyethyleneglycol/potassium phosphate, sodium citrate and ammonium sulphate was assayed using polyethylenglycol of different molecular mass. Pepsin was found to be partitioned towards the polymer-rich phase in all the systems, which suggests an important protein-polymer interaction due to the highly hydrophobic character of the protein surface exposed to the solvent. The pepsin partitioning behavior was explained according to Timasheff's preferential interaction theory. The process was driven entropically with participation of structured water around the polyethyleneglycol ethylenic chains. The best pepsin recovery was observed in the systems polyethyleneglycol molecular mass 600. These systems were chosen in order to assay the bovine stomach homogenate partition and to compare different working conditions such as the top-bottom phase volume ratio and homogenate proportions in the total system. The best purification factors were obtained with PEG600/potassium phosphate with low top-bottom volume ratio using 15% of bovine stomach homogenate in the system total mass.